Two of the same kind?: The Rise of the AfD and its implications for the CDU/CSU - Dilling, M (Berghahn Journals, 2018)
In 2017, the AfD became the first party explicitly positioned to the right of the CDU/CSU to enter the Bundestag since 1957. As the AfD was founded by former CDU members and rose against the backdrop of Merkel’s European and refugee policies, the AfD may appear primarily to threaten the CDU/CSU. I argue that this view is overly simplistic. Analyzing the AfD’s platform, survey data, and factionalism, I find: (1) while the AfD started as a conservative challenger to the Christian Democrats, it moved away from this platform toward becoming a populist radical right party; (2) this transformation is reflected in its vote base, which includes characteristics associated with social conservatism but also encompasses nativist, populist, and even leftwing elements; (3) the AfD has so far been unable to integrate these different positions and stop forces pushing it away from being an option for discontented Christian Democrats.